On four new canopy spiders of Dictynidae (Araneae) from Xishuangbanna Rainforest, China - Zhang, Zhi-Sheng; Li, Shuqiang (Zootaxa, 2011)
Four new Dictynidae species from the rainforest canopy of Xishuangbanna, Yunnan Province, China, are described in the present paper. Two belong to the genus Sudesna Lehtinen, 1967: S. circularis sp. nov. (male, female) and S. digitata sp. nov. (female). And the others are assigned to a new genus, Bannaella gen. nov., which are B. sinuata sp. nov. (female) and B. tibialis sp. nov. (male, female). The new genus is similar to Brommella and Scotolathys in having similar appearances, but can be easily distinguished by the broad dorsal tibial apophysis of the male palp and the simple epigynal ducts of the female. Morphological descriptions, illustrations and photos of all species are given. Additionally, photos of two Chinese species, Brommella punctosparsa (Oi, 1957) from Hunan and Sudesna hedini (Schenkel, 1936) from Guizhou, are also presented, in order to compare with the new genus and the new species of Sudesna.